PENGEMBANGAN LEMBAR KERJA SISWA DALAM PEMBELAJARAN FISIKA BERBASIS RISET DI SMAN 1 PADANG - Usmeldi Usmeldi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Research-based learning in Senior High School (SMAN) 1 Padang implemented through practical activities that are verified theory that has been learned. The results of the preliminary survey of the implementation of learning physics in SMAN 1 Padang showed that teachers have not been using student worksheet (LKS) based on research. There are still many students who have not been thoroughly studied physics. Supporting facilities such as physics lab and equipment already available at SMAN 1 Padang, but has not been used optimally. Research-based learning is a learning model that can improve student learning outcomes. To be able to carry out research based learning, required LKS. This study aims to produce worksheets in learning physics valid research-based, practical, and effective for students of SMAN 1 Padang. Research and development using the 4D model of Thiagarajan. Data collection instrument was an interview guide, observation sheet, sheet validation LKS, LKS practicality questionnaire, and achievement test. The results showed that the BLM had developed a valid category based on expert assessment. LKS including vary practical categories based on the observation, questionnaire responses of teachers and students. LKS use of research-based learning physics, effectively improve the competence of students. Suggested to high school physics teachers in order to implement research-based LKS through a variety of innovative models such as guided inquiry learning, group learning and experiment.Keywords: worksheets, learning physics, research.